Interactive Learning Redefined: How Multimedia Scenario Editors Enhance Immersive Education and Feedback - Salvetti, Fernando; Bertagni, Barbara; Contardo, Ianna (International Journal of Advanced Corporate Learning (iJAC), 2025)
The Multimedia Scenario Editor developed by e-REAL Labs represents a major advancement in experiential learning and simulation-based education. This innovative tool enhances traditional simulation methods by integrating interactive multimedia elements, creating highly immersive and multisensory learning environments. Educators can incorporate visual, auditory, and, in some cases, kinesthetic and olfactory stimuli, significantly enhancing engagement and realism. Its flexible and adaptive design allows for real-time customization, enabling educators to tailor learning experiences to meet individual learner needs. This paper examines the capabilities of the Multimedia Scenario Editor, highlighting its practical applications in simulation-based education and its role in enhancing the debriefing process. Additionally, implementation strategies are discussed, providing educators with actionable insights to maximize the technology’s impact. By enriching educational experiences and fostering deeper learner engagement, the Multimedia Scenario Editor is a comprehensive and scalable solution for modern training environments.